Paleozoic supracrustal rocks near Cheticamp, Nova Scotia - Currie, K. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1982)
Near Cheticamp, northwestern Cape Breton Island, a sequence of supracrustal rocks overlies and cuts granite previously dated at 530+44 million years, as veil as older, presumably Precambrian gneisses. Rhyolite dikes feeding the supracrustal sequence yielded zircons giving a U-Pb dis-cordla age of 439±7 million years (late Ordovician or Silurian). The supracrustal rocks are overlain and cut by bimodal voleantes of the Fisset Brook Formation, previously dated by Rb-Sr isochron at 376±12 million years. Interpretation of the stratigraphic and geochronologlc data, together with petrochemical data on the volcanic rocks, shows that the rocks of the Cape Breton Highland underwent repeated cycles of deformation, uplift and granitic intrusion, rapidly followed by subsidence and emplacement of bimodal volcanic rocks. The repetitive and cyclic nature of the process suggests that throughout late Precambrian and early Paleozoic time these rocks remained in a single, cyclic, tectonic environment, rather than passing from one tectonic environment to another.